Addressing the Natural Resource Curse : An Illustration From Nigeria - Subramanian, Arvind (IMF Working Papers; Working Paper ;, 2003)
Some natural resources-oil and minerals in particular-exert a negative and nonlinear impact on growth via their deleterious impact on institutional quality. We show this result to be very robust. The Nigerian experience provides telling confirmation of this aspect of natural resources. Waste and poor institutional quality stemming from oil appear to have been primarily responsible for Nigeria's poor long-run economic performance. We propose a solution for addressing this resource curse which involves directly distributing the oil revenues to the public. Even with all the difficulties that will no doubt plague its actual implementation, our proposal will, at the least, be vastly superior to the status quo. At best, however, it could fundamentally improve the quality of public institutions and, as a result, durably raise long-run growth performance.